2007
DOI: 10.1532/hsf98.20071089
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Closure Reinforced with Rib Heads: A Novel Technique for Prevention and Treatment of Sternal Dehiscence

Abstract: Early and aggressive debridement of infected and necrotic tissue, irrigation, and antibiotics are necessary for successful treatment, but we believe that the most important factor is full stabilization of the sternal tissue with minimal use of foreign stabilization material. Despite the limited number of cases, we suggest that our stabilization technique seems to be successful in achieving full stabilization even in infected and fragile sternal bony tissue in patients with sternal dehiscence and/or inappropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Ramzisham et al suggested that figure-of-eight sternal closure is equally effective as simple wire suturing in preventing adverse outcomes of sternal dehiscence. 10 Vular et al showed that sternal closure reinforced with rib heads technique is extremely efficient and twenty-two patients from twentythree ones whom were treated with this technique survived 11 while our study showed that figure-eight and simple technique are more related to the risk of morbidity and mortality. 11 Not accessing of association between bone healing and pain scores or complications, and not analyzing of the effect of pain severity on the activity or quality of life were limitations of our study.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Ramzisham et al suggested that figure-of-eight sternal closure is equally effective as simple wire suturing in preventing adverse outcomes of sternal dehiscence. 10 Vular et al showed that sternal closure reinforced with rib heads technique is extremely efficient and twenty-two patients from twentythree ones whom were treated with this technique survived 11 while our study showed that figure-eight and simple technique are more related to the risk of morbidity and mortality. 11 Not accessing of association between bone healing and pain scores or complications, and not analyzing of the effect of pain severity on the activity or quality of life were limitations of our study.…”
Section: Discussionsupporting
confidence: 44%
“…10 Vular et al showed that sternal closure reinforced with rib heads technique is extremely efficient and twenty-two patients from twentythree ones whom were treated with this technique survived 11 while our study showed that figure-eight and simple technique are more related to the risk of morbidity and mortality. 11 Not accessing of association between bone healing and pain scores or complications, and not analyzing of the effect of pain severity on the activity or quality of life were limitations of our study. Finally, we concluded that figure-of-eight can reduce postoperative pain scores and chest re-exploration significantly in diabetic patients with severe obesity (BMI: 35-40) undergoing off-pump CABG surgery.…”
Section: Discussionsupporting
confidence: 44%